RUMAH SAKIT TIPE C DI KECAMATAN PONTIANAK UTARA - Hilmi Khairullah; Muhammad Ridha Alhamdani; Jawas Dwijo Putro (JMARS: Jurnal Mosaik Arsitektur, 2022)
Health is a healthy state of a person who is not only physically but also socially, spiritually and mentally. In every area there must be a health service facility called a hospital. The construction of hospitals in Pontianak City is not so evenly distributed, especially in North Pontianak District. Type C general hospital is a hospital with a capacity of at least 100 inpatient beds, and related to the number of facilities and the ability of specialized medical services at least 4 (four) basic specialists. The approach used in planning a type C hospital is a healing environment approach, which is an approach that combines elements of nature, psychology, and the senses with considerations of site, actors and activities, size of space, architectural elements, structures, utilities. The purpose of this design is the design of a type C hospital that can meet the needs of health facilities in North Pontianak District and the design of a hospital building that is comfortable, safe, and can respond to the surrounding environment by combining natural, psychological, and sensory elements. The methodology used is data collection, data analysis and synthesis, and the design phase. The result of the design of a type C hospital is a hospital building that is comfortable, safe, and able to respond to the surrounding environment by combining natural, psychological, and sensory elements in North Pontianak District.